Measuring the sustainability of wood consumption at the household level in Indonesia: Case study in Bogor, Indonesia - Lutfy Abdulah; Endang Suhendang; Herry Purnomo; Juang Rata Matangaran (Society for Indonesian Biodiversity, 2020)
Abstract. Abdulah L, Suhendang E, Purnomo H, Mattangaran JR. 2020. Measuring the sustainability of wood consumption at the household level in Indonesia: Case study in Bogor, Indonesia. Biodiversitas 21: 457-464. Data on consumption of wood products at the end-user level does not yet exist. This is caused by variations in the shape of wood products and raw materials used. Meanwhile, information on the level of consumption per capita is needed to measure sustainability consumption at the household level, determine the volume of wood production and carbon storage in wood products in the household. The novelty of this study is in method for measure wood product consumption. The aim of this study was to estimate the level of wood consumption at the household level in the form of use for construction and furniture. The method used was a survey of wood products at the industrial level and to make a database and then confirmed to households to determine the level of consumption. The results showed that wood products in the household are divided into 2 main parts namely construction and furniture. The level of wood consumption varied greatly depending on the type of roof, the number of doors and windows and the amount of furniture used. The level of consumption in Bogor reached 0.1 m3 per capita. This consumption was influenced by the time of use and the size of family.